Applying Geomatics Techniques to Study Urban Heat Island Changes in Kirkuk City for the Year 2024 Using Landsat-8 Imagery - Asst.lect Murooj Taher Noaman (Journal of College of Education, 2025)
The urban heat island phenomenon in the city of Kirkuk is one of the significant environmental issues that greatly affect the quality of life. This phenomenon is characterized by higher temperatures in urban areas compared to the surrounding rural areas, due to rapid urban expansion and the use of concrete surfaces such as asphalt and cement, which absorb and retain heat. The lack of green spaces also contributes to exacerbating this issue. Landsat 8 satellite data, equipped with the OLI sensor, was used to monitor the urban heat island and its changes in 2024, with a focus on the four seasons. The data showed that the heat island effect was evident throughout the year, with the hot category occupying the largest percentage during the autumn season (84.91%), while the moderate category dominated during winter at (95.83%), reflecting the overall cooling effect in winter despite the continued presence of the heat island effect. In spring, the moderate category prevailed at (55.95%) due to the gradual transition from winter to summer. During summer, the maximum impact of the urban heat island was observed, with the very hot category reaching (60.54%) due to the extensive presence of hard surfaces that absorb large amounts of heat.In terms of risk classification, the very high-impact category accounted for (24.52%) of the total area, followed by the high-impact category (23.12%), the moderate-impact category (31.53%), and finally the low-impact category (20.84%). The high heat impacts are attributed to urban expansion and the lack of green spaces, while the lower impacts are due to the presence of barren or natural areas that do not contribute to the formation of the heat island, such as green spaces or agricultural lands.